2016
DOI: 10.1111/jog.13051
|View full text |Cite
|
Sign up to set email alerts
|

Fetal nasal bone length at 19–26 weeks’ gestation in Vietnam

Abstract: Aim The purpose of this study was to establish the normal range of fetal nasal bone length (NBL) at the second trimester of gestation in Vietnamese pregnancies. Methods A prospective cross‐sectional study was carried out. A total of 2432 singleton pregnancies were evaluated for fetal NBL at 19–26 weeks 6 days between 1 January 2013 and 31 December 2014. Three measurements of NBL were taken and the largest value was chosen. Fetal anomalies and neonatal abnormalities were excluded. Results Mean fetal NBL was 6.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Nasal bone abnormalities, which include both nasal bone absence and hypoplasia, are commonly used as soft ultrasound markers to screen for Down syndrome during the first or second trimester . A number of studies have shown that fetal nasal bone length grows with advancing gestational age . It is relatively difficult to detect fetal nasal bone during early pregnancy, but the detection becomes easier as the fetus grows.…”
Section: Introductionmentioning
confidence: 99%
“…Nasal bone abnormalities, which include both nasal bone absence and hypoplasia, are commonly used as soft ultrasound markers to screen for Down syndrome during the first or second trimester . A number of studies have shown that fetal nasal bone length grows with advancing gestational age . It is relatively difficult to detect fetal nasal bone during early pregnancy, but the detection becomes easier as the fetus grows.…”
Section: Introductionmentioning
confidence: 99%